PENGARUH PENGETAHUAN DAN MOTIVASI TERHADAP MINAT BERINVESTASI DI PASAR MODAL SYARIAH (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan) - Adinda Rizqi Aryani (Sahmiyya, 2022)
ABSTRACT: This study aims to analyze the influence of knowledge and motivation on student interest in investing in the Islamic capital market. Researches want to see how to much students are interested in investing in stocks or other in the Islamic capital market who in fact do not have experience in this field. The researches want data was made by researches in the form of questions via Google Form and distributed to respondents via the WhatsApp social media network with the acquisition of 20 respondents. The results of these questions were collected and used as material for analysis. Based on the results of the analysis conducted, knowledge and motivation have a significant influence on investment interest in the Islamic capital market.